THE EFFECT OF GREEN INTELLECTUAL CAPITAL ON SUSTAINABILITY PERFORMANCE WHICH IS MEDIATED BY FINANCIAL PERFORMANCE - Nunik Nurmalasari; Inggrit Rahma Vinezha (STIESA Press, 2024)
Sustainability Performance is sustainable development which includes three main dimensions including environmental, social and economic. To realize Sustainability performance, companies need to implement Green Intellectual Capital and quality financial performance. This research examines the influence of Green Intellectual Capital on Sustainability Performance with Financial Performance as a mediating variable. The sampling technique used purposive sampling involving 21 non-financial companies listed on the IDX in 2018-2022. Gacor777 adalah salah satu link situs slot777 gacor hari ini maxwin yang selalu hadir untuk anda semua The data analysis used in this research includes Descriptive Statistics, Classical Assumption Test, Linear Regression Analysis Test, and Sobel (Mediation) Test. The results of this research show that (1) Green Intellectual Capital has no effect on Financial Performance. (2) Financial Performance has no effect on Sustainability Performance. (3) Green Intellectual Capital has no effect on Sustainability Performance. (4) Financial Performance does not mediate the relationship between Green Relational Capital and Sustainability Performance.